Kriteria Lokasi Instalasi Pengolahan Lumpur Tinja dan Optimasi Cakupan Layanan Menggunakan Sistem Informasi Geografis (Studi Kasus Kota Bandung) - Dr. Ahmad Soleh Setiyawan (Jurnal Teknik Lingkungan, 2021)
The location of Faecal Sludge Treatment Plant (FSTP) that is not planned properly can result in a low level of FSTP service, a lack of supply of faecal sludge to the FSTP, and environmental pollution problems due to illegal dumping. In this study, an analysis of important aspects in determining the location of the FSTP and the application of the Geographical Information Systems (GIS) was carried out in optimizing the coverage of FSTP services in Bandung City. The identification of criteria and weight of criteria in determining the FSTP location was performed using a pairwise comparison method against the criteria and sub-criteria obtained from literature review and stakeholders input. The results of the identification criteria were then mapped and analyzed using ArcMAP 10.8.1. Based on the identification results, there are 5 criteria that are declared important in selecting FSTP locations, namely technical, institutional, regulatory and policy, financial, and public acceptance. Further identification of the 5 criteria found 22 sub-criteria and there are 10 sub-criteria including those that can be used in selecting and optimize the service coverage of the FSTP locations in this study. Based on the GIS mapping, an optimum service coverage to serve all areas in Bandung City that has not been served by a wastewater piping system was obtained by using 3 FSTP locations, namely Districts of Gedebage, Cinambo, and Andir with the total required area of 26,400 m2 in 2041. The optimum service coverage is obtained based on the sub-criteria of the shortest distance and the fastest travel time from the FTST location to the farthest service areas.